Hesperetin, a Selective Phosphodiesterase 4 Inhibitor, Effectively Suppresses Ovalbumin-Induced Airway Hyperresponsiveness without Influencing Xylazine/Ketamine-Induced Anesthesia. (13th February 2012) - Shih, Chung-Hung; Lin, Ling-Hung; Hsu, Hsin-Te; Wang, Kuo-Hsien; Lai, Chi-Yin; Chen, Chien-Ming; Ko, Wun-Chang
Abstract : Hesperetin, a selective phosphodiesterase (PDE)4 inhibitor, is present in the traditional Chinese medicine, "Chen Pi." Therefore, we were interested in investigating its effects on ovalbumin- (OVA-) induced airway hyperresponsiveness, and clarifying its rationale for ameliorating asthma and chronic obstructive pulmonary disease (COPD). Hesperetin was revealed to have a therapeutic (PDE4H /PDE4L ) ratio of >11. Hesperetin (10 ~ 30  μ mol/kg, intraperitoneally (i.p.)) dose-dependently and significantly attenuated the airway hyperresponsiveness induced by methacholine. It also significantly suppressed the increases in total inflammatory cells, macrophages, lymphocytes, neutrophils, and eosinophils, and levels of cytokines, including interleukin (IL)-2, IL-4, IL-5, interferon- γ, and tumor necrosis factor- α in bronchoalveolar lavage fluid (BALF). It dose-dependently and significantly suppressed total and OVA-specific immunoglobulin E levels in the BALF and serum. However, hesperetin did not influence xylazine/ketamine-induced anesthesia, suggesting that hesperetin has few or no emetic effects. In conclusion, the rationales for ameliorating allergic asthma and COPD by hesperetin are anti-inflammation, immunoregulation, and bronchodilation.